The Wise Leader's Compass - Ethical Leadership for Success : Incl. Bonus - Ethics, Wisdom and Modern Leadership, How Value-Based Leadership Creates Sustainable Success. - Janson, Simone. (Executive Edition Series, 2026)
Also in the 4th revised and improved edition, published by a government-funded publisher involved in EU programs and a partner of the Federal Ministry of Education, you receive the concentrated expertise of renowned experts (overview in the book preview), embedded in an integrated knowledge system with premium content and 75% advantage.